The Non-random Location of Autosomal Genes That Participate in X Inactivation - Migeon, Barbara R. (Frontiers in Cell and Developmental Biology, 2019)
Mammals compensate for sex differences in the number of X chromosomes by inactivating all but one X chromosome. Although they differ in the details of X inactivation, all mammals use long non-coding RNAs in the silencing process. By transcribing XIST RNA, the human inactive X chromosome has a prime role in X-dosage compensation. Yet, the autosomes also play an important role in the process. Multiple genes on human chromosome 1 interact with XIST RNA to silence the future inactive Xs. Also, it is likely that multiple genes on human chromosome 19 prevent the silencing of the single active X – a highly dosage sensitive process. Previous studies of the organization of chromosomes in the nucleus and their genomic interactions indicate that most contacts are intra-chromosomal. Co-ordinate transcription and dosage regulation can be achieved by clustering of genes and mingling of interacting chromosomes in 3D space.. Unlike the genes on chromosome 1, those within the critical eight MB region of chromosome 19, have remained together in all mammals assayed, except rodents, indicating that their proximity in non-rodent mammals is evolutionarily conserved. I propose that the autosomal genes that play key roles in the process of X inactivation are non-randomly distributed in the genome and that this arrangement facilitates their coordinate regulation.